Prevalence of Cardiac Risk Factors in Patients Prescribed Azithromycin before and after the 2012 FDA Warning on the Risk of Potentially Fatal Heart Rhythms. Issue 2 (14th January 2020) - Patel, Haridarshan; Calip, Gregory Sampang; DiDomenico, Robert J.; Schumock, Glen T.; Suda, Katie J.; Lee, Todd A.
Abstract : Study Objective: To measure the prevalence of cardiac risk factors among patients prescribed azithromycin before and after the United States Food and Drug Administration (FDA) issued a warning on May 17, 2012, on the risk of potentially fatal heart rhythms associated with the drug. Design: Retrospective cohort study using administrative claims data. Data Source: Truven Health Analytics MarketScan database. Patients: A total of 12, 971, 078 unique patients with 23, 749, 652 azithromycin prescriptions dispensed between January 2009 and June 2015 were included. Patients had to be continuously enrolled in a health plan for at least 365 days (baseline) before the date of azithromycin dispensing (index date). Cohorts were assigned based on the index dates of the azithromycin prescriptions, either before (January 1, 2009–May 1, 2012) or after (June 1, 2012–June 30, 2015) the FDA warning was issued. Measurements and Main Results: A cardiac risk factor included either a cardiac condition (heart failure or dysrhythmias) or concurrent use of drugs that prolong the QT interval. The unit of analysis was each prescription of azithromycin. Multivariable logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the prevalence of cardiac risk factors. Mean age of the patients was 40.1 ± 21.3 years old, with 60.8% females. Prior to the FDA warning, 11, 596, 022 (48.8%) azithromycin prescriptions were identified, and 12, 153, 630 (51.2%) were identified after the warning. The prevalence of a preexisting cardiac condition was 7.3% versus 7.9% (p<0.0001) before and after the FDA warning, respectively. Concurrent use of a QT‐interval–prolonging drug was 23.3% versus 24.2% (p<0.0001) before and after the FDA warning, respectively. After controlling for confounders, the odds of having a cardiac risk factor after the FDA warning were significantly lower (odds ratio 0.938, 95% CI 0.936–0.940) compared with before the FDA warning. Conclusion: Despite the 2012 FDA warning, a nontrivial number of azithromycin prescriptions was prescribed concurrently in patients with preexisting a cardiac condition (1 of 12 azithromycin prescriptions) and in those using a QT‐interval–prolonging drug (1 of 5 azithromycin prescriptions). After adjusting for confounders, the odds of cardiac risk factors being present in patients prescribed azithromycin were modestly lower after the warning; however, the prevalence remained essentially unchanged before and after the FDA warning was issued.